Forecasting Search Trends for “Silverqueen” Chocolate Keywords using the Singular Spectrum Analysis Method and the Hybrid Singular Spectrum Analysis-ARIMA Model - Gavrila Nathania Rambung; Sri Wahyuningsih; Andrea Tri Rian Dani (Science & Technology Asia, 2024)
This research uses a hybrid model of time series in the process. The Singular Spectrum Analysis (SSA) method will be combined with the Autoregressive Integrated Moving Average (ARIMA) method to model noise from SSA. This research applied the hybrid SSA-ARIMA method to Google Trends data, especially to the chocolate keyword "Silverqueen" search trend. This research aims to assess the accuracy and identify the best forecasting method for search trends for the keyword "Silverqueen" chocolate in Indonesia. Based on the results, the accuracy value obtained for the SSA method was 0.54% (MAPE) and 0.04 (RMSE) for in-sample data and 28.93% (MAPE) and 1.49 (RMSE) for out-sample data. The hybrid SSA-ARIMA (5.1.0) method has two outliers with an accuracy value of 0.35% (MAPE) and 0.02 (RMSE) for insample data and 31.00% (MAPE) and 1.50 (RMSE) for out-sample data. The results of the SSA forecasting method for the next 17 periods show that the trend will increase, with the highest trend occurring in the second week of February 2024, namely 100 points. Then, the forecast results of the hybrid SSA-ARIMA(5,1,0) method with outliers for the next 17 periods, the trend will increase, with the highest trend occurring in the second week of February 2024, namely around 95 points. The best method for forecasting search trends for the chocolate keyword “Silverqueen” is the SSA method.